PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD - Dewi Nurkhasanah; Wahyudi Wahyudi; Endang Indarini (Satya Widya, 2019)
This study aims to describe the increase of critical thinking skills in learning Mathematics of fifth-grade students in SD N Noborejo 01 Argomulya sub-district, Salatiga. This study is a spiral action class study of the Mc. Taggart model which consists of 2 cycles, where each cycle has 4 stages, namely the stages of planning, acting, observing, and reflecting, however at the acting and observing stages were carried out at the same time. The data collection techniques carried out in this study were observation and tests. The instruments used were the observation sheet of teacher and student activities as well as a test sheet for students’ critical thinking skills. Data analysis was performed using comparative descriptive analysis, this was done by comparing the pre-cycle, cycle I and cycle II. The researcher determined the success indicator of 80% of students completing with the Minimum Criteria of Mastery Learning ≥ 70. The results showed that by applying the Problem Based Learning model students’ critical thinking skills in mathematics subjects can be improved, where it was shown that in the first cycle students’ critical thinking skills was 58.98% and in the second cycle, it increased to 97.44%. The number of students who completed the pre-cycle was 15 (38.5%) students, where it increased to 22 (56.4%) students in cycle I and increased again to 33 (84.6%) students in cycle II. The research can be said successful because it has reached a success indicator of 80% of all fifth-grade students who completed the Minimum Criteria of Mastery Learning ≥ 70. Based on these results, research with Problem Based Learning learning models can improve students’ critical thinking skills thus it influences student learning outcomes on the subject of mathematics.